Pengaruh Opini Publik di Media Sosial terhadap Independensi Hakim dalam Memutus Suatu Perkara (Perspektif Rule of Law dan Rule of Ethics) - Kholilur Rahman; Markus Suryoutomo; Muhammad Saiful Islam (PSHPM Untag Semarang, 2025)
The current digital era, the use of social media has proliferated, where many people use social media such as Facebook, Instagram, Twitter, or other media to express their opinions. Moreover, as stated in Article 28 E of the 1945 Constitution, freedom of expression has been guaranteed by law that everyone has the freedom to associate, assemble, and express opinions. This study will discuss the impact of public opinion through social media on the integrity of judges in making decisions (in the perspective of the rule of law and the rule of ethics). Because, in principle, judges must, of course, be based on relevant facts and legal rules that are used as a juridical basis in making decisions. Not being swept away in public opinion and/or not being influenced by issues that develop on social media because unfair decisions will have an impact on the judiciary and the people who are affected by the decision. So, in this case, the profession of judges is tied to the rule of law and the rule of ethics, which basically aims to maintain the dignity of judges and the nobility of the profession of judges. The research method used is normative, using statutory, conceptual, and case study approaches.